KONDISI KLENÈNGAN GAYA SURAKATA DI WILAYAH SOLO RAYA (2000-2017) - Suyoto suyoto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2017)
AbstractThis research focuses on the condition of Surakarta style karawitan that is performed independently, also known as klenèngan, in the Greater Solo district. The research uses a musicological perspective and analyzes various aspects related to an ideal klenèngan performance. In accordance with the developments in the present era, the condition of klenèngan in the Greater Solo district has experienced a significant development in terms of its quantity. From the point of view of quality, aspects such as form, packaging of gending, and concept of patet are given insufficient attention in the performance of klenèngan in the Greater Solo district, and as a result, an ideal klenèngan performance has not been achieved. The results of this research show that in order to achieve an ideal klenèngan performance, there are a number of determining criteria, such as: (1) condition of the gamelan, (2) place and position of the gamelan, (3) sufficient number of musicians, (4) time, (5) continuity of performance, and (6) weather.  Keywords: gamelan, klenèngan, ideal. Abstrak Penelitian ini difokuskan pada kondisi karawitan gaya Surakarta yang bersifat mandiri yang disebut klenèngan, di wilayah Solo Raya. Penelitian ini  menggunakan perspektif musikologis, dengan menganalisis berbagai aspek berkaitan dengan penyajian klenèngan yang ideal. Sesuai dengan perkembangan zaman kondisi sajian klenèngan di wilayah Solo Raya dalam kehidupannya dari tahun ke tahun secara kuantitas telah mengalami perkembangan yang cukup signifikan.  Sajian klenèngan di wilayah Solo Raya,  pada umumnya secara kualitas terutama bentuk, kemasan gending, konsep patet kurang diperhatikan, sehingga  tidak  dicapai sajian klenèngan yang ideal.  Hasil penelitian ini ditemukan bahwa untuk mencapai sajian klenèngan yang ideal terdapat beberapa kreteria antara lain, (1) kondisi gamelan, (2) tempat dan posisi gamelan, (3) kelengkapan pengrawit, (4) waktu, (5) kelancaran sajian, dan (6) cuaca. Kata Kunci: gamelan, klenèngan, ideal